2017
DOI: 10.1177/1358863x17694091
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in utilization and outcomes of catheter-directed thrombolysis in patients with proximal lower extremity deep venous thrombosis – Insights from the Nationwide Inpatient Sample

Abstract: Catheter-directed thrombolysis (CDT) is being increasingly used for the treatment of proximal lower extremity (LE) deep venous thrombosis (DVT). However, sex differences in utilization and safety outcomes of CDT in these patients are unknown. The Nationwide Inpatient Sample (NIS) database was used to identify all patients with a principal discharge diagnosis of proximal LE or caval DVT who underwent CDT between January 2005 and December 2011 in the United States. We evaluated the comparative safety outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…However, bleeding-related mortality and overall mortality were no different between the sexes. Concurrent with previous literature, this analysis suggests that treatment modalities for DVT using CDT and systemic thrombolysis differ between sexes with females less likely to undergo CDT for DVT 19 There have been fewer studies regarding sex differences in the utilization of CDT for PE, but the present study suggest that sex-based trends in CDT for DVT may be applicable to PE. On the other hand, Geibel et al showed that males and females received similar rates of systemic thrombolysis for submassive PE, although they reported much higher rates of thrombolysis in their cohort.…”
Section: Discussionsupporting
confidence: 74%
“…However, bleeding-related mortality and overall mortality were no different between the sexes. Concurrent with previous literature, this analysis suggests that treatment modalities for DVT using CDT and systemic thrombolysis differ between sexes with females less likely to undergo CDT for DVT 19 There have been fewer studies regarding sex differences in the utilization of CDT for PE, but the present study suggest that sex-based trends in CDT for DVT may be applicable to PE. On the other hand, Geibel et al showed that males and females received similar rates of systemic thrombolysis for submassive PE, although they reported much higher rates of thrombolysis in their cohort.…”
Section: Discussionsupporting
confidence: 74%
“…No previous studies have investigated sex differences in the risk of bleeding from CDT in ALI, but a previous study comparing the use of CDT in lower limb or caval deep venous thrombosis found an increased need for blood transfusion in female patients, but a reduced incidence of intracranial and gastrointestinal bleeding. 25 In the propensity score adjusted analysis, female sex was associated with a reduced odds of undergoing a fasciotomy. This may be attributed to that acute compartment syndrome is more unrecognized and underdiagnosed in females or that females do not develop acute compartment as often as men.…”
Section: Discussionmentioning
confidence: 95%
“…The lack of significant difference may be due to insufficient power of the current study, but may also be due to meticulous adjustment of heparin administration in response to repeated measurments of activated clotting time. No previous studies have investigated sex differences in the risk of bleeding from CDT in ALI, but a previous study comparing the use of CDT in lower limb or caval deep venous thrombosis found an increased need for blood transfusion in female patients, but a reduced incidence of intracranial and gastrointestinal bleeding 25 …”
Section: Discussionmentioning
confidence: 99%
“…10 These patients tend to visit their physician more frequently and to require more intensive care coordination from the practice between visits. Given differences in healthcare utilization between men and women, [39][40][41] it was interesting to note that gender was not associated with receiving CCM services in this analysis. Race/ethnicity, however, was associated with receipt of CCM services.…”
Section: Discussionmentioning
confidence: 99%